Long COVID headache - Tana, Claudio; Bentivegna, Enrico; Cho, Soo-Jin; Harriott, Andrea M.; García-Azorín, David; Labastida-Ramirez, Alejandro; Ornello, Raffaele; Raffaelli, Bianca; Beltrán, Eloísa Rubio; Ruscheweyh, Ruth; Martelletti, Paolo (Journal of headache and pain, 2022)
Headache is among the most frequent symptoms persisting or newly developing after coronavirus disease 2019 (COVID-19) as part of the so-called long COVID syndrome. The knowledge on long COVID headache is still limited, however growing evidence is defining the features of this novel condition, in particular regarding clinical characteristics, some pathophysiological mechanisms and first treatment recommendations. Long COVID headache can present in the form of worsening of a preexisting primary headache, or, more specifically, in the form of a new (intermittent or daily) headache starting during the acute infection or after a delay. It often presents together with other long COVID symptoms, most frequently with hyposmia. It can manifest with a migrainous or, more frequently, with a tension-type-like phenotype. Persistent activation of the immune system and trigeminovascular activation are thought to play a role. As there are virtually no treatment studies, treatment currently is largely guided by the existing guidelines for primary headaches with the corresponding phenotype. The present report, a collaborative work of the international group of the Junior Editorial Board of The Journal of Headache and Pain aims to summarize the most recent evidence about long COVID headache and suggests approaches to the diagnosis and treatment of this disorder. Graphical Abstract